PERENCANAAN KEUANGAN UNTUK MENINGKATKAN LITERASI KEUANGAN PADA PT. CJ LOGISTIK CIKARANG - Cakranegara, Pandu Adi; Liswandi, Liswandi; Rahadi, Dedi Rianto (POLITEKNIK LP3I JAKARTA, 2025)
The community service conducted at PT CJ Logistic is an effort to support financial literacy. This is necessary because CJ Logistic employees are young people who joined the company immediately after graduating from vocational high school. Many of them are working at this company for the first time. Therefore, there is a need to provide financial literacy knowledge to the workers at this company. To facilitate the event and avoid disrupting work hours, the event was held on Saturday when the company only operates half a day. The community service was conducted by organizing a short educational session on personal financial planning. The session was divided into two parts: in the first session, participants received classroom instruction. In the second session, participants were encouraged to ask questions about their individual financial planning. Of course, creating a personal financial plan requires knowledge of one's financial condition and time to develop it. Therefore, the second session focused on general financial planning. At the end of the session, a summary of what was learned that day was provided, and the event concluded with a game related to financial planning led by the students. Participants attended the session from start to finish with enthusiasm. It is hoped that the knowledge gained from this training will be applied in their daily lives.